Evaluation of quality of life in patients with systemic sclerosis by the SF-36 questionnaire - R. Cossutta; S. Zeni; A. Soldi; P. Colombelli; A. Belotti Masserini; F. Fantini (PAGEPress Publications, 2002)
Aims: to evaluate the quality of life of patients affected by systemic sclerosis (SSc) through the application of the Medical Outcome Survey Short-Form 36 (SF-36) questionnaire and to correlate the results with the disability index of the health assessment questionnaire (HAQ-DI) and the systemic involvement. Methods: we studied 95 (3 M, 91 F) patients affected by SSc (mean age 60 years, range 39-83, mean duration of disease 6 years, range 1-34). The organ system involvement was evaluated by skin score, chest High Resolution Computed Tomography (HRCT), electrocardiography according to Holter, Doppler-echocardiography and oesofagogram. Results: considering the values of the 8 question groups of the SF-36 the most different between the patients and the control population are the values relevant to the physical dimension. The general health values estimating the physical and social dimension are significantly lower in the patients than in the control population (t=9,324; p<0,0001). A very good correlation was found between the DI (r = -0,7903 ; p <0.0001) and all the scores of SF-36. The skin involvement showed a statistically significant correlation with the DI (r=0.3709; p=0.0002) and the PA score of the SF- 36 (r =0.2853; p=0.0051). No other statistically significant correlation was found between any of the SF-36 dimensions and involvement of a specific organ. Conclusion: SF-36 showed to be a valid instrument to evaluate the quality of life and the disability of patients with SSc and it seems to correlate with extent of skin involvement.